Uncovering Active Constituents Responsible for Different Activities of Raw and Steamed Panax notoginseng Roots - Xiong, Yin; Chen, Lijuan; Hu, Yupiao; Cui, Xiuming (Frontiers in Pharmacology, 2017)
Although Panax notoginseng (PN) roots in raw and steamed forms were historically supposed to be different in the efficacies, the raw materials and steamed ones were often undifferentiated in the use and market circulation, which might bring unstable curative effects or even adverse reactions. To uncover chemical constituents responsible to different activities of raw and steamed PN, chemometrics analyses including partial least squares regression and multi-linear regression analysis were used to establish the relationships between the chromatographic fingerprints and activities of PN samples. Chemical fingerprints of PN were determined by HPLC. Anticoagulant and antioxidant activities were evaluated by the thromboplastin inhibiting test and hydroxyl radical scavenging assay, respectively. Results showed that there was a significant difference in the chemical composition between raw and steamed PN, which could be discriminated by principle component analysis according to different steaming temperatures. Compared with the steamed PN, raw PN exhibited stronger anticoagulation and weaker antioxidation. By chemometrics analyses, notoginsenoside R1, ginsenosides Rg1, Re, Rb1, and Rd were found to be the major active constituents of raw PN, whereas ginsenosides Rh1, Rk3, Rh4, and 20(R)-Rg3 had the key role in the activities of steamed PN, which could be used as new markers for the quality control of steamed PN.